1983
DOI: 10.1017/s0043174500068491
|View full text |Cite
|
Sign up to set email alerts
|

Ivyleaf Morningglory (Ipomoea hederacea) Control with Herbicides in Soybeans (Glycine max)

Abstract: When trifluralin [α,α,α - trifluoro - 2,6 - dinitro -N,N-dipropyl-p-toluidine] was manually incorporated in small field plots to a depth of 10 cm, ivyleaf morningglory [Ipomoea hederacea(L.) Jacq.] was controlled more effectively than when incorporation was only 5 cm deep. No significant differences in ivyleaf morningglory control were observed between different incorporation depths when trifluralin was mechanically incorporated in large field plots. Ivyleaf morningglory emerging from 10 cm deep was controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
2
0

Year Published

1988
1988
1988
1988

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 5 publications
2
2
0
Order By: Relevance
“…lacunosa L.) morningglory. Prosch and Kapusta (1983) have reported similar results. There have been reports, however, of an interaction between dinitroanilines and substituted amides in controlling morningglory.…”
supporting
confidence: 61%
See 3 more Smart Citations
“…lacunosa L.) morningglory. Prosch and Kapusta (1983) have reported similar results. There have been reports, however, of an interaction between dinitroanilines and substituted amides in controlling morningglory.…”
supporting
confidence: 61%
“…Metzer et al (1974) reported that a preplant incorporated application of trifluralin followed by a preemergence application of alachlor gave greater than 90% control ofivyleafmorningglory in cotton (Gossypium hirsutum L.). Prosch and Kapusta (1983) reported similar findings in soybean and identified this as a synergistic effect. High levels of jimsonweed and velvetleaf control were also noted.…”
supporting
confidence: 52%
See 2 more Smart Citations